The Business Fallout from the Rapid Obsolescence and Planned Obsolescence of High-Tech Products: Downsizing of Noncompetition Agreements - Hodges, Ann C.; Taylor, Porcher L. (Science and Technology Law Review, 2005)
The recent rapid pace of technological change has made human capital more important, yet it has rendered the employee’s knowledge base obsolete more quickly. Employers use covenants not to compete, restricting employees from switching to work for competitors, in order to retain knowledgeable personnel. Currently, the lack of predictability in interpreting noncompete agreements allows employers to draft overly-lengthy noncompetes, encourages enforcement litigation, and curtails employees from changing jobs because of the fear of litigation. Employees should not be prevented from working for competitors for longer than is necessary to protect the employer’s legitimate interest. Use of obsolescence as a guide in drafting noncompete agreements should provide the protection employers need without overburdening the employee’s option to change jobs. Judges should utilize court-appointed obsolescence experts in order to determine the useful life of employee knowledge and should limit noncompete agreements accordingly. This judicial scrutiny should encourage employers to tie restrictions directly to obsolescence of employee knowledge, improving both predictability and fairness of noncompete agreements.